L-Cysteine-Derived H2S Promotes Microglia M2 Polarization via Activation of the AMPK Pathway in Hypoxia-Ischemic Neonatal Mice - Zhou, Xin; Chu, Xili; Xin, Danqing; Li, Tingting; Bai, Xuemei; Qiu, Jie; Yuan, Hongtao; Liu, Dexiang; Wang, Dachuan; Wang, Zhen (Frontiers in Molecular Neuroscience, 2019)
We have reported previously that L-cysteine-derived hydrogen sulfide (H2S) demonstrates a remarkable neuroprotective effect against hypoxia-ischemic (HI) insult in neonatal animals. Here, we assessed some of the mechanisms of this protection as exerted by L-cysteine. Specifically, we examined the capacity for L-cysteine to stimulate microglial polarization of the M2 phenotype and its modulation of complement expression in response to HI in neonatal mice. L-cysteine treatment suppressed the production of inflammatory cytokines, while dramatically up-regulating levels of anti-inflammatory cytokines in the damaged cortex. This L-cysteine administration promoted the conversion of microglia from an inflammatory M1 to an anti-inflammatory M2 phenotype, an effect which was associated with inhibiting the p38 and/or JNK pro-inflammatory pathways, nuclear factor-κB activation and a decrease in HI-derived levels of the C1q, C3a and C3a complement receptor proteins. Notably, blockade of H2S-production clearly prevented L-cysteine-mediated M2 polarization and complement expression. L-cysteine also inhibited neuronal apoptosis as induced by conditioned media from activated M1 microglia in vitro. We also show that L-cysteine promoted AMP-activated protein kinase (AMPK) activation and the AMPK inhibitor abolished these anti-apoptotic and anti-inflammatory effects of L-cysteine. Taken together, our findings demonstrate that L-cysteine-derived H2S attenuated neuronal apoptosis after HI and suggest that these effects, in part, result from enhancing microglia M2 polarization and modulating complement expression via AMPK activation.